Correction of Cobalamin Malabsorption in Pancreatic Insufficiency with a Cobalamin Analogue that Binds with High Affinity to R Protein but not to Intrinsic Factor: IN VIVO EVIDENCE THAT A FAILURE TO PARTIALLY DEGRADE R PROTEIN IS RESPONSIBLE FOR COBALAMIN MALABSORPTION IN PANCREATIC INSUFFICIENCY - Allen, Robert H.; Seetharam, Bellur; Allen, Nancy C.; Podell, Elaine R.; Alpers, David H. (The Journal of Clinical Investigation, 1978)
In vitro studies indicate that [57Co]cobalamin (Cbl) is preferentially bound to salivary R protein as opposed to intrinsic factor (IF) and that [57Co]Cbl bound to R protein is not transferred to IF at either pH 2 or pH 8. Incubation of R protein-[57Co]Cbl with pancreatic proteases causes a partial degradation of the R protein moiety and a rapid transfer of [57Co]Cbl to IF. We have postulated that the etiology of Cbl malabsorption in pancreatic insufficiency is an inability to partially degrade R protein because of a lack of pancreatic proteases. We have tested this hypothesis by determining the ability of a nonradioactive Cbl analogue, bound with high affinity by R protein but not by IF, to correct the malabsorption of [57Co]Cbl in patients with pancreatic insufficiency. R protein bound the Cbl analogue known as cobinamide with affinities that were the same and only 14-fold lower than those for Cbl at pH 8 and pH 2, respectively. Cobinamide was bound by IF with affinities that were 600,000- and 10,000-fold lower than those for Cbl at pH 8 and 2, respectively. The addition of 125 pmol of nonradioactive cobinamide to 0.5 pmol of [57Co]Cbl before being added to 1 pmol of R protein and 1 pmol of IF, markedly inhibited the ability of R protein to compete with IF for binding the [57Co]Cbl. Similar results were obtained with freshly aspirated gastric juice. This change was essentially indistinguishable from that observed previously when R protein or R protein-[57Co]Cbl was incubated in vitro with trypsin. The oral administration of 100 nmol of nonradioactive cobinamide in Schilling tests was equivalent to trypsin in its ability to completely correct the malabsorption of 0.4 nmol of [57Co]Cbl in three patients with pancreatic insufficiency. The fact that both trypsin and nonradioactive cobinamide inhibit the ability of R protein to compete with IF for [57Co]Cbl binding in vitro, and correct the mal-absorption of [57Co]Cbl in patients with pancreatic insufficiency in vivo, supports our hypothesis that the primary defect in Cbl absorption in this disease is an inability to partially degrade R protein because of a lack of pancreatic proteases.